Association between sedentary behavior, obesity and hypertension in public school teachers - Delfino, Leandro Dragueta [UNESP]; Tebar, William Rodrigues [UNESP]; Tebar, Fernanda Caroline Staquecini Gil [UNESP]; DE SOUZA, Jefferson Marinho [UNESP]; Romanzini, Marcelo; Fernandes, Rômulo Araújo [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (National Institute of Industrial Health, 2020)
The present study aimed to verify the prevalence and association of sedentary behavior and its breaks with obesity and cardiovascular risk factors in teaching professionals. The sample was composed by 245 public school teachers (186 women and 59 men), with a mean age of 45 yr. Sedentary behavior was evaluated by self-reported screen time in different devices (television, computer, cellphone/tablet), and sedentary breaks at work and leisure were assessed by a Likert scale (never, rarely, sometimes, often, always). Cardiovascular risk factors (overweight/obesity, abdominal obesity, blood pressure, and heart rate) were objectively collected by trained individu-als in the work environment of the teachers. Logistic Binary Regression models were adjusted for confounding factors (age, sex, and socioeconomic status). The prevalence of sedentary behavior was 55.3% in the sample. High sedentary behavior was associated to abdominal obesity (OR=2.21 [CI=1.23–3.97]). No association was observed between sedentary breaks at work and independent variables, however teachers with high sedentary breaks at leisure time were less likely to present high blood pressure (OR=0.58 [CI=0.32–0.98]). In conclusion, high sedentary behavior was associated with abdominal obesity, and high sedentary breaks in leisure time were associated to lower chances of high blood pressure among public school teachers.
Keywords: Abdominal Obesity; Blood pressure; Screen time; Sedentary breaks; Teachers